IMPLEMENTATION OF THE PRINCIPLES OF GOOD GOVERNANCE IN COMBATING STUNTING IN THE JABON DISTRICT, SIDOARJO REGENCY - Alifa Asta Sabilla; Arimurti Kriswibowo (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Jabon District is one of the sub-districts in Sidoarjo Regency which is still facing the problem of high stunting cases. Many factors can cause stunting, low access to nutritious food, vitamins, poor parenting, and low health awareness. The impact arising from stunting is the low quality of human resources, because Not only does it inhibit physical growth (stunted/stunted), but also inhibits brain development and low-thinking ability, thereby inhibiting future demographic bonuses. To overcome this, good governance actors (government, private sector, community) are needed in its implementation. These actors, namely the government of the Sidoarjo Regency Health Service and the Jabon Health Center are collaborating with other actors from the private sector (Perusahaan Gas Negara) and the community (Umsida). This study aims to determine the implementation of the principles of good governance in tackling stunting in Jabon District, Sidoarjo Regency. There are 8 principles of good governance according to UNDP, namely: 1. participation, 2. rule of law, 3. transparency, 4. responsiveness, 5. oriented to consensus, 6. justice, 7. effectiveness and efficiency, 8. accountability, 9. strategic vision. The type of research used is descriptive qualitative. The result of this research is that the implementation of principles of good governance has been implemented although there are still some principles that are not optimal. The conclusion of the implementation of the principles of good governance according to UNDP has been implemented and is still ongoing, but the resulting impact has not been maximally felt.